ATP-sensitive potassium channels alter glycolytic flux to modulate cortical activity and sleep - Nicholas J. Constantino; Caitlin M. Carroll; Holden C. Williams; Hemendra J. Vekaria; Carla M. Yuede; Kai Saito; Patrick W. Sheehan; J. Andy Snipes; Marcus E. Raichle; Erik S. Musiek; Patrick G. Sullivan; Josh M. Morganti; et al. (Proceedings of the National Academy of Sciences, 2025)
Metabolism plays a key role in the maintenance of sleep/wake states. Brain lactate fluctuations are a biomarker of sleep/wake transitions, where increased interstitial fluid (ISF) lactate levels are associated with wakefulness and decreased ISF lactate is required for sleep. ATP-sensitive potassium (K ATP ) channels couple glucose-lactate metabolism with excitability. Using mice lacking K ATP channel activity (e.g., Kir6.2 −/− mice), we explored how changes in glucose utilization affect cortical electroencephalography (EEG) activity and sleep/wake homeostasis. In the brain, Kir6.2 −/− mice shunt glucose toward glycolysis, reducing neurotransmitter biosynthesis and dampening cortical EEG activity. Kir6.2 −/− mice spent more time awake at the onset of the light period due to altered ISF lactate dynamics. Together, we show that Kir6.2-K ATP channels act as metabolic sensors to gate arousal by maintaining the metabolic stability of sleep/wake states and providing the metabolic flexibility to transition between states.